Ulnar nerve innervation of the medial mead of the triceps brachii muscle: A cadaveric study - Loukas, Marios; Bellary, Sharath; Yüzbaşıoğlu, Neslihan; Shoja, Mohammadali; Tubbs, Shane; Spinner, Robert (Wiley-Blackwell, 2013)
Although the ulnar nerve is closely associated with the triceps brachii muscle, the literature does not normally describe it as supplying this muscle. However, recent research has examined the ulnar nerve in the upper arm and identified branches supplying the medial head of the triceps brachii muscle. This study aims to expand upon this research by describing the course and incidence of these branches in a larger sample size. We examined 50 specimens in 25 cadavers. Ulnar innervation of the medial head of the triceps brachii was identified in 14 specimens (28%). The mean distance of the ulnar nerve branch midpoint was 26% along a line between the surgical neck and an epicondyle line, with a range of 11-39%. Innervation of the triceps brachii muscle by the ulnar nerve has important clinical and surgical implications. Clin. Anat. 26:1028-1030, 2013.
WOS: 000326036600023
PubMed ID: 23716143
Keywords: Ulnar Nerve; Triceps Brachii; Medial Head of Triceps